A multicentre point prevalence survey (PPS) of antimicrobial use amongst admitted patients in tertiary care centres in India. (11th January 2021) - Panditrao, Aditi M; Shafiq, Nusrat; Chatterjee, Suparna; Pathak, Ashish; Trivedi, Niyati; Sadasivam, Balakrishnan; Kshirsagar, Nilima; Kaul, Rajni; Biswal, Manisha; Kakkar, Ashish; Malhotra, Samir; Arora, Pankaj; et al.
Abstract: Objectives: Data from point prevalence surveys (PPSs) in India are scarce. Conducting PPSs is especially challenging in the absence of electronic medical records, a lack of dedicated resources and a high patient load in resource-poor settings. This multicentre survey was conducted to provide background data for planning and strengthening antimicrobial stewardship programmes across the country. Methods: This inpatient PPS was conducted over 2 weeks in May 2019 simultaneously across five study centres in India. Data about patient characteristics, indications for antimicrobials use and details of each antimicrobial prescribed including supportive investigation reports were collected in predesigned forms. Results: A total of 3473 admitted patients in wards and ICUs were covered across five study centres. Of these, 1747 (50.3%) patients were on antimicrobials, with 46.9% patients being on two or more antimicrobials. Out of the total antimicrobials prescribed, 40.2% of the antimicrobials were prescribed for community-acquired infection requiring hospitalization followed by surgical prophylaxis (32.6%). Third-generation cephalosporins and drugs from the 'Watch' category were prescribed most commonly. Only 22.8% of the antimicrobials were based on microbiology reports. Conclusions: The survey demonstrated a high use of antimicrobials in admitted patients with a considerable proportion of drugs from the 'Watch' category. The targets for interventions that emerged from the survey were: improving surgical prophylaxis, decreasing double anaerobic cover, initiating culture of sending cultures and de-escalation with targeted therapy.